Electrochemical reduction of NaBO2 into NaBH4 with pulse voltage using the Eu-Co-Ni-B coating electrode. Issue 2 (1st February 2022) - Zhang, Shimin; Chen, Biqing; Gao, Lixia; Xiong, Tongtong; Du, Chan; Zhu, Yunna; Zhao, Jing
Abstract: To further explore the possibility of the electrochemical reduction of NaBO2 into NaBH4, the electrochemical reduction of NaBO2 into NaBH4 was fulfilled with pulse voltage using the Eu-Co-Ni-B coating electrode. A simple electroless plating technique was used to prepare the Eu-Co-Ni-B coating electrode. It has been proved that NaBO2 was converted into NaBH4 by electrochemical analysis method. The results showed that the method of detection and quantitative analysis of NaBH4 with gold electrode was feasible (R 2 =0.98). When the reverse pulse voltage was + 0.5 V, the forward pulse voltage was −1.5 V, the reverse pulse duration was 2 s and the forward pulse duration was 2 s, the concentration of NaBH4 reaches a maximum of 1.25 × 10 −4  mol/L. With the continuous increase of electrolytic time, the concentration of NaBH4 shows a trend of increasing first and then decreasing. When the electrolytic time was 2 h, the maximum concentration of NaBH4 reaches 1.61 × 10 −4  mol/L. Graphical Abstract: UF0001